Assessing the Direct Impact of Typhoons on Vegetation Canopy Structure and Photosynthesis - Yaoyao Zheng; Simin Zhan; Zaichun Zhu; Sen Cao; Jiana Chen; Pengjun Zhao; Weimin Wang; Ranga B. Myneni (Journal of Remote Sensing)
Typhoons are undergoing changes in frequency, intensity, and landward movement due to climate change, placing coastal vegetation ecosystems at heightened risk. These ecosystems provide critical ecological, social, and economic functions, making accurate assessment of typhoon impacts essential for effective management and disaster risk reduction. Traditional methods for assessing typhoon impacts on large-scale vegetation often compare pre- and post-typhoon satellite images. These do not account for natural variations in plant life cycles or interannual variations in environmental conditions, potentially leading to inaccurate assessments of typhoon-induced vegetation damage and recovery. This study proposes a novel framework for quantifying typhoons’ immediate and long-term impacts on vegetation canopy structure and photosynthesis. We developed random forest models based on satellite-observed leaf area index (LAI) and environmental data during typhoon-free periods to simulate LAI under non-typhoon conditions. The simulated LAI time series was then compared with the satellite-observed typhoon-affected LAI to assess the typhoon-induced canopy loss and recovery, which was then used to estimate the typhoon-caused photosynthesis loss and recovery with 2 widely used light-use efficiency models. The framework was applied to 3 super typhoons that traversed the Greater Bay Area. Typhoons Nida, Hato, and Mangkhut caused canopy losses in 76.58%, 61.25%, and 89.67% of vegetated regions, respectively, leading to direct cumulative gross primary production losses of 0.36, 0.22, and 0.50 Tg C. The proposed framework establishes a pivotal foundation for future modeling and assessment of direct vegetation damage attributed to typhoons, providing scientific support for vegetation management and disaster risk reduction in coastal areas.